Rice starch multi-level structure and functional relationships. (1st January 2022) - Zhong, Yuyue; Qu, Jianzhou; Li, Zhihang; Tian, Yu; Zhu, Fan; Blennow, Andreas; Liu, Xingxun
Abstract: Starch from 15 different rice genotypes with amylose content (AC) ranging 1.5%–30.6% were investigated for relationships between structures and properties. For parameters related to the granular level, the most important relationships were found for AC, average chain lengths (ACL) of the amylopectin (AP) fb1 chains having a length of DP 13-24, crystallinity, and the thickness of the crystalline (dc ) and the amorphous lamellae (da ) of the starch granule. AC and dc were negatively correlated with the peak gelatinization temperature (Tp ), thermal enthalpy (ΔH), and peak viscosity (PV), but positively correlated with swelling power. ACLfb1 and da, as compared to AC and dc, had the opposite effects on these parameters, demonstrating important roles of specific molecular and lamellar structures on the starch granular stability. For the gelatinized systems, increasing ACLfb1 decreased retrogradation, while AC increased retrogradation by increasing the resistant starch (RS) content, storage modulus ( G′ ), and setback (SB). Graphical abstract: Unlabelled Image Highlights: Short (fb1 ) amylopectin chains is crucial for pasting, digestion, and rheology. Crystalline and lamellar structure is important for thermal and pasting properties. Amylose content is positively correlated with peak viscosity. Long fb1 chains leads to thermal resistance and low peak viscosity and resistant starch content. Short amylose chains is conceivably the main leaching chains during heating.